Hydration in thermo-responsive oligoether methacrylate hydrogels studied by FT-IR spectroscopy. (3rd May 2021) - Piechocki, Krzysztof; Kozanecki, Marcin
Abstract: Hydration in thermo-responsive polymer hydrogels, such us poly(oligo(ethylene glycol) methyl ether methacrylates) (POEGMAs) is a key factor in understanding their thermo-responsivity. The hydration of POEGMAs with different length of side groups was comprehensively studied for the first time. The comparative studies have shown that hydration of different hydrophilic centres in various POEGMAs is similar and independent of oligoether chain length. Only some quantitative differences in bound water structure, especially at the first stage of hydration have been found. However, the crystallinity (if it occurs) significantly impacts on the hydration process. Finally, the water structure is the closer to the bulk water structure in the fully swollen PMEO2 MA hydrogel than in other POEGMA systems with longer oligoether side groups. Graphical abstract: Image 1 Highlights: POEGMA hydrogels differing on oligoether side chain length were studied by FTIR. The differences in their hydration was shown for the first time. Water-water and polymer-water interactions were studied in function of H2 O content. Depending on crystallinity three- or two-step mechanism of hydration was found. Also, an impact of the length of side hydrophilic group on hydration was studied.